United Nations Disarmament Yearbook 2020: Part II - United Nations Office for Disarmament Affairs (United Nations, 2021)
This publication summarizes developments and trends in 2020 on key issues of multilateral consideration at the international and regional levels. The yearbook reviews the activity of the General Assembly and the Conference on Disarmament and the Disarmament Commission. Additionally, it contains a timeline that highlights events in multilateral disarmament in 2020 and comprises a foreword written by the High Representative for Disarmament Affairs.